Comparison of Accuracy Levels in Financial Distress Prediction Models using Altman Z-Score, Zmijewski, and Springate - Sutardjo, Abdul Wahid; Andarwati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine the accuracy rate of potential financial distress using three financial distress prediction models (Altman Z-Score, Zmijewski, Springate) to predict financial distress for E512 sector tourism companies (hotels, resorts, and cruise ships) listed on the Indonesia Stock Exchange for 2019-2023. This type of research is descriptive quantitative. The data source used in this study is secondary data. The findings from the study show that Zmijewski's model outperforms the other two models with an accuracy rate of 93.3% in estimating financial distress. On the other hand, the accuracy of the Altman Z-Score model is at a moderate level with a rate of 46%, followed by the Springate model which is the lowest with an accuracy rate of 8% each. The conclusion reached by this study is that the Zmijewski model is the instrument with the highest percentage of accuracy and can be recommended for estimating the financial difficulties of tourism companies. However, the output of this study can only be recommended as a warning signal and not a definitive bankruptcy forecast. The results of this study are likely to provide insight into the evaluation of investors, creditors, and stakeholders on the financial condition of E512 (Hotels, Resorts, & Cruise) tourism companies listed on the Indonesia Stock Exchange.